Strategi Dakwah Multimedia Nahdlatul Ulama melalui Instagram @nuonline_id - Santoso , Bobby Rachman; Fatmasari , Lutfi; Nurcholis , Ahmad (Al-Insyiroh: Jurnal Studi Keislaman, 2021)
Da’wah media from time to time continue to experience such good development. The emergence of social media in the community has also influenced the delivery of da'wah messages. In this case, preachers is required to be able to use social media as a medium for preaching. This research is motivated by the use of Instagram as a medium for preaching, especially the Nahdlatul Ulama organization. This research was conducted on the official Nahdlatul Ulama Instagram account, @nuonline_id. This study aims to understand how the format of the da'wah message presented by the @nuonline_id account and how the da'wah strategy used by Nahdlatul Ulama on the @nuonline_id account. Qualitative research was chosen to be the research method in this study. In addition, the approach used is a phenomenological approach. In this study, the results show that @nuonline_id has 2 strategies in preaching through Instagram, namely: first, in presenting images with insertions of words and selecting templates that show the characteristics of Nahdlatul Ulama. Second, presenting a video with an interesting concept.